2014
DOI: 10.1007/s12223-014-0330-6
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia due to Enterobacter cancerogenus infection

Abstract: Enterobacter cancerogenus (formerly known as CDC Enteric Group 19; synonym with Enterobacter taylorae) has rarely been associated with human infections, and little is known regarding the epidemiology and clinical significance of this organism. We describe a community-acquired pneumonia case in a 44-year-old female due to E. cancerogenus. Identification and antimicrobial susceptibility of the microorganism was performed by the automatized VITEK 2 Compact system (bioMerieux, France). The clinical case suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In immunocompromised patients, it is paramount to maintain a This pathogen is intrinsically resistant to beta-lactams and cephalosporins. 5 In this particular case, the source of infection remains uncertain, in the absence of documented bacteremia or other risk factors it is presumed to be secondary to contamination of the surgical field. No other cases have been documented at our center.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In immunocompromised patients, it is paramount to maintain a This pathogen is intrinsically resistant to beta-lactams and cephalosporins. 5 In this particular case, the source of infection remains uncertain, in the absence of documented bacteremia or other risk factors it is presumed to be secondary to contamination of the surgical field. No other cases have been documented at our center.…”
Section: Discussionmentioning
confidence: 94%
“…This is the first case report, to our knowledge, citing E. cancerogenus as the cause of a pericardial abscess post heart transplantation. This pathogen is intrinsically resistant to beta‐lactams and cephalosporins . In this particular case, the source of infection remains uncertain, in the absence of documented bacteremia or other risk factors it is presumed to be secondary to contamination of the surgical field.…”
Section: Discussionmentioning
confidence: 99%
“…Metataxonomics revealed that only three known microbial species were shared by all five bat species. Two of these were pathogenic and can cause brain abscesses associated with conditions such as meningitis, osteomyelitis, and pneumonia ( 47 49 ). These species were E. cancerogenus and C. freundii , which have been detected or isolated from Dendrolimu kikuchii and pollen ( 50 , 51 ), Hyalessa maculaticollis , Galleria mellonella ( 52 , 53 ), and leafhoppers, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the actual mortality rate caused by E. cancerogenus infection is lower because the mortality rate may be more closely related to the trauma itself rather than to the resulting E. cancerogenus infection. In addition, there have been case reports of E. cancerogenus causing osteomyelitis ( 3 ) bacteremia ( 7 ), urinary tract infection ( 8 ), and pneumonia ( 9 ). The pathogenicity of this organism remains unknown, therefore, further studies are needed to clarify the clinical characteristics of infections due to E. cancerogenus .…”
Section: Discussionmentioning
confidence: 99%